2021
DOI: 10.3390/molecules26092632
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins Recovered from Agri-Food By-Products Using Innovative Processes: Trends, Challenges, and Perspectives for Their Application in Food Systems

Abstract: Anthocyanins are naturally occurring phytochemicals that have attracted growing interest from consumers and the food industry due to their multiple biological properties and technological applications. Nevertheless, conventional extraction techniques based on thermal technologies can compromise both the recovery and stability of anthocyanins, reducing their global yield and/or limiting their application in food systems. The current review provides an overview of the main innovative processes (e.g., pulsed elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 195 publications
(312 reference statements)
0
24
0
Order By: Relevance
“…Anthocyanin molecules are highly unstable and easily degraded by enzymes, light, temperature, pH and oxygen concentration; these factors prove a challenge to the recovery processes [ 6 , 12 ]. Method selection should consider the cost, versatility, method complexity, extractability and preservation of the target compounds [ 12 , 13 ].…”
Section: Sources Of Anthocyaninsmentioning
confidence: 99%
See 3 more Smart Citations
“…Anthocyanin molecules are highly unstable and easily degraded by enzymes, light, temperature, pH and oxygen concentration; these factors prove a challenge to the recovery processes [ 6 , 12 ]. Method selection should consider the cost, versatility, method complexity, extractability and preservation of the target compounds [ 12 , 13 ].…”
Section: Sources Of Anthocyaninsmentioning
confidence: 99%
“…Anthocyanin molecules are highly unstable and easily degraded by enzymes, light, temperature, pH and oxygen concentration; these factors prove a challenge to the recovery processes [ 6 , 12 ]. Method selection should consider the cost, versatility, method complexity, extractability and preservation of the target compounds [ 12 , 13 ]. An example of anthocyanin recovery from blackcurrant pomace is the use of acidified water extraction followed by a solid-phase extraction with sequential liquid–liquid aqueous-organic partitioning to separate monomeric and polymeric anthocyanins as well as flavonoids.…”
Section: Sources Of Anthocyaninsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently concluded that berry by-products from processing steps are a cheap and available source for isolating anthocyanins-rich extracts using non-thermal processing technologies as can be observed in Table 2 . These technologies have been demonstrated to have unique characteristics such as being effective, rapid, low-cost, and eco-friendly [ 106 , 107 ]. It is essential to highlight that the accuracy of the technique depends on not only the conditions or the matrix of the F&V by-products.…”
Section: Effect Of Non-thermal Technologies On Fruit and Vegetable By-products Pigmentsmentioning
confidence: 99%